Characterization of the genetic variation present in CYP3A4 in three South African populations - Drögemöller, Britt I.; Plummer, Marieth; Korkie, Lundi; Agenbag, Gloudi; Dunaiski, Anke; Niehaus, Dana; Koen, Liezl; Gebhardt, Stefan; Schneider, Nicol; Olckers, Antonel; Wright, Galen; Warnich, Louise (Frontiers in Genetics, 2013)
TThe CYP3A4 enzyme is the most abundant human cytochrome P450 and is regarded as the most important enzyme involved in drug metabolism. Inter-individual and inter-population variability in gene expression and enzyme activity are thought to be influenced, in part, by genetic variation. Although Southern African individuals have been shown to exhibit the highest levels of genetic diversity, they have been under-represented in pharmacogenetic research to date. Therefore, the aim of this study was to identify genetic variation within CYP3A4 in three South African population groups comprising of 29 Khoisan, 65 Xhosa and 65 Mixed Ancestry individuals. To identify known and novel CYP3A4 variants, 15 individuals were randomly selected from each of the population groups for bi-directional Sanger sequencing of approximately 600 bp of the 5’-upstream region and all thirteen exons including flanking intronic regions. Genetic variants detected were genotyped in the rest of the cohort. In total, 24 SNPs were detected, including CYP3A4*12, CYP3A4*15, and the reportedly functional CYP3A4*1B promoter polymorphism, as well as two novel non-synonymous variants. These putatively functional variants, p.R162W and p.Q200H, were present in two of the three populations and all three populations, respectively, and in silico analysis predicted that the former would damage the protein product. Furthermore, the three populations were shown to exhibit distinct genetic profiles. These results confirm that South African populations show unique patterns of variation in the genes encoding xenobiotic metabolizing enzymes. This research suggests that population-specific genetic profiles for CYP3A4 and other drug metabolizing genes would be essential to make full use of pharmacogenetics in Southern Africa. Further investigation is needed to determine if the identified genetic variants influence CYP3A4 metabolism phenotype in these populations.